2012
DOI: 10.1089/chi.2011.0061
|View full text |Cite
|
Sign up to set email alerts
|

Participation in the Child and Adult Care Food Program Is Associated with More Nutritious Foods and Beverages in Child Care

Abstract: CACFP participation may be one means by which reimbursement for food can be increased and food offerings improved. Further research should investigate whether promoting CACFP participation can be used to provide healthier nutrition environments in child care and prevent obesity in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 13 publications
9
82
0
Order By: Relevance
“…Existing obesity prevention educational curricula (e.g., the Preschool Obesity Prevention Series) (Miller et al, 2012) seek to enhance children's behavioral regulation skills, but educational materials focused on enhancing children's regulatory skills specific to the childcare context are lacking. CACFP participation has been associated with improved nutritional quality of foods and beverages served in childcare centers (Ritchie et al, 2012) and among low-income children, has been shown to moderately increase consumption of milk and vegetables (Korenman, Abner, Kaestner, & Gordon, 2012). The CACFP recommendations could be further leveraged to help prevent childhood obesity by placing a greater emphasis on the development of training materials for improving childcare providers' use of responsive feeding practices that support children's self-regulation of their energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…Existing obesity prevention educational curricula (e.g., the Preschool Obesity Prevention Series) (Miller et al, 2012) seek to enhance children's behavioral regulation skills, but educational materials focused on enhancing children's regulatory skills specific to the childcare context are lacking. CACFP participation has been associated with improved nutritional quality of foods and beverages served in childcare centers (Ritchie et al, 2012) and among low-income children, has been shown to moderately increase consumption of milk and vegetables (Korenman, Abner, Kaestner, & Gordon, 2012). The CACFP recommendations could be further leveraged to help prevent childhood obesity by placing a greater emphasis on the development of training materials for improving childcare providers' use of responsive feeding practices that support children's self-regulation of their energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used in 2012 were the same as those used in the 2008 study. 13 The study was deemed exempt by the Committee for the Protection of Human Subjects at the University of California, Berkeley.…”
Section: Methodsmentioning
confidence: 99%
“…12 During 2008, we evaluated the beverages served in a statewide sample of child-care sites in California and identified need for improvement concerning the provision of water, serving lower-fat milk, and limiting juice. 13 Child-care sites can elect to participate in the federal Child and Adult Care Food Program (CACFP), which provides reimbursement for meals and snacks served daily to more than 3 million children. 14,15 More than one in nine children in CACFP reside in California.…”
mentioning
confidence: 99%
“…We found that directors are aware of food costs and compare prices among healthy foods with up to 20 % opting for a less healthy food choice because it is more affordable. In a recent study, directors reported that nutritional content, cost, availability, and convenience were all factors that affected what foods were served to children [28].…”
Section: Director Attitudes Regarding Nutritionmentioning
confidence: 99%